Abstrakt graficzny – nowy czy jedynie odświeżony gatunek tekstu naukowego? - ŁASZKIEWICZ, MONIKA (Stylistyka, 2025)
The article compares the traditional textual abstracts (monomodal) with graphical abstracts (multimodal), which are becoming an increasingly popular form of presenting key information contained in an article. The material basis consisted of 150 abstracts representing various fields of knowledge, functioning together with the article texts in one document or independently of them (e.g., in abstract books). The genre analysis was conducted using the genre description parameters of J. Bartmiński and S. Niebrzegowska-Bartmińska (sender, recipient, communication situation, communication intention, topic, ontology of the presented world, form and manner of presenting the topic, values) and revealed that graphical abstracts are a special genre that can facilitate the understanding of scientific texts, accelerate the memorisation of key content, and popularise research findings. Visual abstracts differ in the way they connect graphics (words, paratext, or text) with images (drawings, diagrams, graphics). They combine not only a cognitive value but also an aesthetic value, which is new in the case of scientific texts.